Pengaruh Ukuran Perusahaan, Struktur Aktiva, Likuiditas, Dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (2020-2022) - Jessy Safitri Sitorus; Marisa Silvia Tiurma Putri; Octaviani Barus; Khanti Listya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study was conducted with the aim of knowing the effect of company size, asset structure, liquidity and sales growth on capital structure. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period as many as 87 company samples. The analysis method used in this research is multiple linear regression analysis with SPSS application tools. This study uses data in the form of annual financial reports from each sample company published on the website www.idx.co.id. Simultaneously, the variable of company size, asset structure, liquidity and sales growth affect the capital structure. Furthermore, the result of t test in this research shows that 1) firm size has negative and significant effect on capital structure, 2) asset structure has positive and significant effect on capital structure, 3) liquidity has negative and significant effect on capital structure, 4) sales growth has positive and significant effect on capital structure.